Conscientiousness but not agreeableness mediates females' tendency toward being a morning person. Issue 3 (June 2017) - Rahafar, Arash; Castellana, Ina; Randler, Christoph; Antúnez, Juan Manuel
Abstract : Individuals differ in their chronotype, and some are identified as morning ones and others as evening ones. Earlier studies showed that women were higher on morningness, conscientiousness, and agreeableness. In this study, we aimed at exploring the mediational effects of conscientiousness and agreeableness in the relationship of gender and morningness‐eveningness. Participants were 669 university students. Results supported positive relationships between morningness and conscientiousness and agreeableness and between conscientiousness and agreeableness. Females were higher on all these three variables. Mediation analyses suggested that the effect of gender (here females) on chronotype (here morningness) was mediated by conscientiousness but not agreeableness so that after the mediation partially occurred, the gender's effect did not remain significant anymore. This study backed our hypothesis that conscientiousness might play a more pronounced role than the intrinsic diurnal rhythm concerning the sex differences in chronotype.